INFLUENCE OF WORD OF MOUTH, LOCATION, AND PRICE ON PURCHASING DECISIONS AT ALANG ISA RESTAURANT - Ferdi, Wayan; Patmarina, Hepiana (Distribusi - Journal of Management and Business, 2026)
The culinary industry is characterized by intense competition, making it essential for business owners to understand what drives consumers to choose one restaurant over another. Factors such as word of mouth, location, and price play a crucial role in shaping purchasing decisions. This study focuses on Alang Isa Restaurant in Bandar Lampung and examines how these three factors influence consumer behavior. Using a quantitative research approach, data were collected from restaurant customers. Since the total number of consumers was unknown, 100 respondents were selected as the sample based on the Lemeshow formula with a 10 percent margin of error. The results of the analysis show that word of mouth, location, and price significantly affect purchasing decisions, both individually and collectively. These findings indicate that customer recommendations, a strategically accessible location, and competitive pricing are key elements in Alang Isa Restaurant’s ability to attract new customers and retain existing ones. Together, these factors contribute to higher customer satisfaction and encourage consistent purchasing behavior.